Dari Tanda ke Makna: Eksplorasi Semiotika Al-Qur'an dengan Teori Peirce - Imam Muslim Amin; Muliadi Muliadi; Wildan Taufiq (PT. Student Rihlah Indonesia, 2026)
This study explores the application of Charles Sanders Peirce’s semiotic theory in interpreting the meanings and symbolism embedded within the Qur'an. Utilizing a semiotic approach, the research aims to examine how signs in the Qur'anic text function as mediums for conveying profound divine messages. It focuses on the triadic relationship between sign, object, and interpretant in the context of revelation, and how this structure influences the spiritual and moral understanding of the Muslim community. Through an in-depth analysis of selected verses rich in symbolic content, the study reveals that Qur'anic signs are not merely representational but also transcendental in nature—serving as bridges that connect surface meanings to deeper theological insights. The findings indicate that Peirce’s semiotic framework offers a valuable contribution to the field of Qur'anic exegesis, especially in analyzing the dynamic nature of meaning, the structure of signs, and the relevance of symbols in religious life. Accordingly, this study highlights the importance of integrating linguistic and spiritual approaches in the interpretation of sacred texts, providing deeper insights into divine revelation and enriching the religious experience of believers.